Implications of Outsourcing - Investigating the Nature of Quality of Service Provided by an Offshore Outsourcee - Zu, Hongli (2008)
Since higher service quality would lead to increased customer satisfaction, and that would yield profit in business, there has been a growing interest of measuring service quality. The purpose of this dissertation is to investigate the nature of quality of service provided by Chinese supplier in the offshore outsourcing context. This research use the different quality dimensions to examine the gap between outsourcer's expected and perceived quality of service. Totally seventeen organizations from western country participate this research. Two questionnaires for each outsourcing company to obtain information, aim to evaluating the ES (Expected Service Quality) and PS (Perceived Service quality) provided by their Chinese outsourcee. In order of acquire more detailed information, an face to face interview with British Telecom (BT) and an in-depth interview with Sofmit which is the No. 1 of Chinese west IT company was conducted. Certain kinds of quality dimensions based on the factors derived from literature review will be employed to measure the discrepancy of ES and PS quality.